# How do you differentiate #g(x) = (1/(x^3-1))*sqrt(1+e^(x))# using the product rule?

##### 1 Answer

#### Answer:

#### Explanation:

The product rule states: if

#g(x) = f(x) * h(x)# ,

the derivative of

#g'(x) = f'(x) * h(x) + f(x) * h'(x)#

In your case,

#f(x) = 1 / (x^3 - 1) " "# and

#h(x) = sqrt(1 + e^x)#

The first thing you need to do is differentiate

=====================

Let's start with

#f(x) = 1/u# where#u = x^3 -1#

According to the chain rule, the derivative is the derivative of

# [1/u]' = [u^(-1)]' = - u^(-2) = - 1 / u^2 = - 1/(x^3 -1)^2#

# [x^3 -1 ]' = 3x^2#

Thus,

#f'(x) = - 1 / (x^3 - 1)^2 * 3x^2 = - (3x^2) / (x^3 - 1)^2#

=====================

Now, you still need to differentiate

#h(x) = sqrt(v)# where#v= 1 + e^x#

The derivative of

#[sqrt(v)]' = [v^(1/2)]' = 1/2 v^(-1/2) = 1 / (2sqrt(v)) = 1 / (2sqrt(1 + e^x))#

# [1 + e^x]' = e^x#

This means that the derivative of

#h'(x) = 1 / (2sqrt(1 + e^x)) * e^x = e^x / (2sqrt(1 + e^x))#

=====================

Now, the only thing left to do is applying the product rule:

#g'(x) = f'(x) * h(x) + f(x) * h'(x)#

# color(white)(xxxiii) = - (3x^2) / (x^3 - 1)^2 * sqrt(1 + e^x) + 1 / (x^3 - 1) * e^x / (2sqrt(1 + e^x))#

# color(white)(xxxiii) = - (3x^2 sqrt(1 + e^x) )/ (x^3 - 1)^2 + e^x / ( 2sqrt(1 + e^x)(x^3 - 1))#